Description of Males from Three Species of Eumeninae (Hymenoptera, Vespidae) - Grandinete, Y. C. [UNESP]; Noll, F. B. [UNESP]; Lopes, R. B. [UNESP] (Springer Nature, 2017)
The external morphology and genitalia of the males of Stenonartonia mimica (Kohl 1907), Sphaeromenes discrepatus Giordani Soika, 1978 and Gamma bolivianum flavior Giordani Soika, 1990 are described for the first time.
Keywords: male genitalia; mason wasps; Potter wasps; solitary wasps